(untitled) (Journal of Renal and Hepatic Disorders, 2020)
Therapeutic apheresis is an extracorporeal treatment that selectively separates abnormal cells or substances from the blood that are linked with or cause certain disease states. It is widely used in transplantation medicine as an adjunctive therapeutic option. In kidney transplantation (KT), recurrent and de novo glomerular diseases represent the third most common cause of graft failure beyond the first year after transplantation, as current therapeutic options are limited. Evidence to support the use of therapeutic apheresis in these conditions is scarce, as it is only supported by observational studies. The purpose of this review was to examine and clarify the potential role of therapeutic apheresis and describe current evidence in the treatment of recurrent and de novo glomerular diseases after KT.